A requirement for astrocyte IP3R2 signaling for whisker experience-dependent depression and homeostatic upregulation in the mouse barrel cortex - Butcher, John B.; Sims, Robert E.; Ngum, Neville M.; Bazzari, Amjad H.; Jenkins, Stuart I.; King, Marianne; Hill, Eric J.; Nagel, David A.; Fox, Kevin; Parri, H. Rheinallt; Glazewski, Stanislaw (Frontiers in Cellular Neuroscience, 2022)
Changes to sensory experience results in plasticity of synapses in the cortex. This Experience-dependent plasticity (EDP) is a fundamental property of the brain. Yet, while much is known about neuronal roles in EDP, very little is known about the role of astrocytes. To address this issue, we used the well-described mouse whiskers-to-barrels cortex system, which expresses a number of forms of EDP. We found that all whisker deprivation induced characteristic experience-dependent Hebbian depression (EDHD) followed by homeostatic upregulation in L2/3 barrel cortex of wild type mice. However, these changes were not seen in mutant animals (IP3R2-/-) that lack the astrocyte expressed IP3 receptor subtype. A separate paradigm, the single whisker experience, induced potentiation of whisker induced response in both WT mice and IP3R2-/- mice. Recordings in ex vivo barrel cortex slices reflected the in vivo results so that long term depression (LTD) could not be elicited in slices from IP3R2-/- mice, but long-term potentiation (LTP) could. Interestingly, 1Hz stimulation inducing long-term depression in WT paradoxically resulted in NMDAR-dependent LTP in slices from IP3R2-/- animals. The LTD to LTP switch was mimicked by acute buffering astrocytic [Ca2+]i in WT slices. Both WT LTD and IP3R2-/- 1Hz LTP were mediated by non-ionotropic NMDAR signaling but only WT LTD was P38 MAPK dependent, indicating an underlying mechanistic switch. These results demonstrate a critical role for astrocytic [Ca2+]i in several experience-dependent plasticity mechanisms in neocortex.